ANALISIS FUNDAMENTAL DALAM KEPUTUSAN INVESTASI SAHAM DI PASAR MODAL (SUB SEKTOR PERBANKAN 2020) - Habibati Sayyidatu Cahyani (2022)
Investment is a productive activity as an alternative form of a person to achieve welfare goals in the future. Stocks are one of the investment instruments in the capital market that are in great demand by investors, because the level of profit obtained is very attractive. Stock analysis is used as a measure for investors to obtain accurate information about the company's actual financial, business, and operational performance. In conducting stock analysis, there are two approaches, namely fundamental analysis and technical analysis. Where with these two approaches, it will be able to help make it easier for investors to make decisions in their stock investment activities. The purpose of this final project is to determine the use of fundamental analysis of the banking sub-sector consisting of economic analysis, industry analysis and company analysis. The results of this paper show that with a fundamental analysis approach, the banking sub-sector is suitable for investment in the long term.